# Answer on Algebra Question for shelby

Question #16140

-9+8(9x-8)=-1+7(12x+12)

Expert's answer

-9+8(9x-8)=-1+7(12x+12)

-9 + 8*9x – 8*8 = -1 + 7*12x + 7*12

72x – 73 = 84x + 83

72x – 84x = 83 + 73

-12x = 156

X = -13

-9 + 8*9x – 8*8 = -1 + 7*12x + 7*12

72x – 73 = 84x + 83

72x – 84x = 83 + 73

-12x = 156

X = -13

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment